Architectural Stimuli in the Perception of Urban Residents - Vazieva, Alfiya R.; Valieva, Regina Z. (Journal of History Culture and Art Research, 2019)
The work is devoted to the study of social frustration and emotional reactions of citizens to architectural stimuli. It addresses the issues of differences in the level of social frustration of young and adult citizens and the relationship between social frustration and emotional responses to architectural stimuli. This study is relevant to the activities of practical psychologists, in personnel work with the staff, in the work of consulting centers, and other areas of work with people. Results and conclusions of the study emphasize the importance of the philosophical and anthropological parameters of the urban population, that cоuld be used by urban self-government in making various administrative decisions and the development of short- and long-term programs for the development of the city in various kinds of ideological actions.